THEORETICAL FOUNDATIONS OF WORD FORMATION IN THE RUSSIAN AND UZBEK LANGUAGES - Sultanmuradova Farangiz Akramovna; Kudratova Gulruh Izzatullaevna. (Scholar Express Journals, 2023)
This article discusses the features of word formation in the Russian and Uzbek languages. The article is mainly discussed on the basis of antonymy
Keywords: Russian language; Uzbek language; word formation; antonymy